Identity and Representation of Dalit Consciousness in Ahuti's Poetry - Shah, Harijang (Journal of Musikot Campus, 2024)
In the presented article, the identity and representation of Dalit consciousness in Ahuti's poetry is studied and analyzed. As the data obtained in the article are explained and analyzed descriptively and analytically, its format is qualitative. All the materials that are related to the study or written in Nepali literature that represent the Dalit consciousness and are necessary for the solution of academic problems have been collected from the library sources. As it is a qualitative research, deductive, analytical and logical processes have been used especially for interpretive analysis. In this way, the poet Ahuti, who has emerged in the contemporary progressive poetry stream, has not written so many poems in terms of quantity, but his poems are very strong and powerful in terms of quality. Ahuti, who literally followed the principles of progressive poetry writing, not only strongly opposed caste oppression, but also analyzed the problems of Dalits in a very academic manner and presented solutions. Ahuti has presented the identity and representation of Dalits against discrimination in Nepali literature in a very powerful way by exposing the rebellion against social distortions and disharmony, repression, exploitation, caste discrimination by the capitalist class towards Dalits and the oppressed in his poetry. In this way, by including his poetry in the school curriculum and textbooks, it has been concluded that everyone in the society needs to change their attitude and attitude towards Dalits from a young age.